Uso de sistema de integração lavoura - pecuária na recuperação de áreas compactadas: Riacho dos Cavalos PB - Melo, Reginaldo Tavares de (Universidade Federal Rural do Semi-Árido, 2011)
The semi-arid region of the Brazilian northeast, besides presenting few resources, is subject to droughts that seriously affect the crop and the grazing productivity. The use of residues left by the cultures, as well as the reduction of the soil conventional cultivation system (plowing and harrowing) it is techniques that can improve the soil structure. The evidences have been showing that the agricultural production systems, highly mechanized, have been influenced by the soil compaction. This can be determined by the great variation in the physical properties of the soil, such as, bulk density, structural porosity and relation tension-deformation. The system of integration production crop-livestock allows alternatives of rotations of cultures and systems of production making possible, the intensification of the use of the land, increasing the sustainable agriculture production systems and improving the profitability through the introduction of the annual grazing. This project aimed to value the effect of the system of integration production crop-livestock cultivation sequential on the soil structure at an agricultural property under cultivation of corn and bean, as well as he valued the effect of the soil physical and mechanical properties at the agricultural production system. The experiment system was established at a agriculture property Riacho dos Cavalos PB (06°26 34 S and 37°39 03 W) 200 m above the sea level and annual precipitation of 850 mm. The parameters of bulk density, textural density, structural void ratio and soil compression ratio and soil resistance penetration were analyzed in the depth from 0.0 to 0.05 m, 0.05 to 0.10 m and 0.10 to 0.20 m. The delineation in blocks at random was used in scheme factorial 2x3x3. The results did not show up significant differences of bulk density between the system crop-livestock. The soil with grazing after the cultivation of corn, it presented reduction in the structural void ratio. The structural void ratio decrease with the increase of the water content and with the increase of the bulk density. The climatic conditions did not allow getting production of culture.
Use of the tilling - livestock integration system at the recuperation of the compacted grounds areas at Riacho dos Cavalos PB.
Keywords: Productivity; sustainability; profitability; Produtividade; sustentabilidade; rentabilidade; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO